Determination Of The Seller's Absence In The Sale And Purchase Agreement Of Land Ownership Rights - Nanang Fayakun; Setiyowati; Edy Lisdiyono (Warmadewa Press, 2024)
This study investigates the legal implications of the seller's absence in a land ownership rights sale and purchase agreement, focusing on a case where the seller's whereabouts were unknown. The research examines Court Ruling Number 52/Pdt.P/2014/PN Mkd, which declared the seller, Nur Rochman, absent and appointed his father, Sarkam, to represent him in the sale of his land. The ruling is analyzed from the perspective of legal certainty, judicial reasoning, and its alignment with the Civil Code. Based on literature and legal regulations, the normative juridical method is used to address legal uncertainties related to the seller's absence. The study highlights the process of transferring land ownership rights under Indonesian law when the seller is declared absent and raises concerns about future claims by the original owner. It concludes with suggestions for improving the legal framework to ensure greater certainty in such transactions.